Association of Oscillatory Ventilation during Cardiopulmonary Test to Clinical and Functional Variables of Chronic Heart Failure Patients - Reis, Hugo Valverde (2018)
Objective: The aim of this study is to characterize the presence of exercise oscillatory ventilation (EOV) and to relate it with other cardiopulmonary exercise test (CET) responses and clinical variables. Methods: Forty-six male patients (age: 53.1 +/- 13.6 years old